Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.2147/ceg.s103485
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal reflux disease symptoms in the Greek general population: prevalence and risk factors

Abstract: Background and aimsPopulation-based data regarding the prevalence of gastroesophageal reflux disease (GERD) in Greece are very poor. This study estimated the prevalence of GERD symptoms and their risk factors in the Greek adult population.MethodsA self-administered questionnaire was answered by a randomly selected population of 340 subjects. The question regarding “heartburn, chest pain, indigestion, or stomach acid coming up” as included in the Reflux Symptom Index was used for prevalence assessment.ResultsTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 39 publications
(48 reference statements)
3
15
0
1
Order By: Relevance
“…Sixty-nine studies reported the duration of symptoms required to meet criteria for gastro-oesophageal reflux, with 36 using 12 months,11 24 28 29 31 32 35–37 41 42 46–48 56 62 65 67 69 70 73 74 77 79–83 86 94 100 102 104 107 111 115 6 using 6 months,19 34 38 51 71 101 11 using 3 months,23 26 33 39 40 43 44 52 60 87 109 7 using 1 month53 64 78 88 92 106 118 and 9 using 1 week 27 59 66 84 99 105 112 114 117. The prevalence of gastro-oesophageal reflux symptoms was highest in studies that used a 1-month timeframe (20.1%), but was also higher in studies that used 6 months, compared with those that used 12 months (17.6% vs 14.1%) (table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sixty-nine studies reported the duration of symptoms required to meet criteria for gastro-oesophageal reflux, with 36 using 12 months,11 24 28 29 31 32 35–37 41 42 46–48 56 62 65 67 69 70 73 74 77 79–83 86 94 100 102 104 107 111 115 6 using 6 months,19 34 38 51 71 101 11 using 3 months,23 26 33 39 40 43 44 52 60 87 109 7 using 1 month53 64 78 88 92 106 118 and 9 using 1 week 27 59 66 84 99 105 112 114 117. The prevalence of gastro-oesophageal reflux symptoms was highest in studies that used a 1-month timeframe (20.1%), but was also higher in studies that used 6 months, compared with those that used 12 months (17.6% vs 14.1%) (table 2).…”
Section: Resultsmentioning
confidence: 99%
“…In the remaining studies, 30 used a postal questionnaire,19–23 25–27 29 32 36 37 39 54 56 60–62 64 66 69 75 78 81 94 97 100 106 111 118 22 conducted a face-to-face interview,11 31 33 41 45 53 58 59 63 65 67 70 71 76 91 95 99 101 103 107 115 117 16 used a self-completed questionnaire (including internet-based questionnaires),24 35 44 48 50 77 84 85 87–90 96 110 112 114 17 used an interview-administered questionnaire28 30 38 51 55 57 73 80 82 83 86 92 98 102 104 116 119 and 16 used a questionnaire completed during a telephone interview 34 40 42 43 46 47 49 52 68 72 74 79 93 105 108 109. Pooled prevalence of gastro-oesophageal reflux symptoms was highest in the 30 studies that used a postal q...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a more recent study on GERD prevalence and risk factors on a global scale, the prevalence varied according to country from 2.5% in a Chinese to 51.2% in a Greek study [8]. Whereas the validated gastroesophageal reflux disease questionnaire (GERDQ) was used in the Chinese study, the Greek study employed the reflux symptom index [9,10]. In the Persian gulf and Middle East regions, higher rates have been reported; 18 to 21% in Iran, 19 to 25% in Turkey and 29% in Saudi Arabia [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…It can be observed in studies conducted by Bhatia et al, Fujiwara et al, Minatsuki et al and Nilsson et al [9][10][11][12] In a study conducted by Spantideas et al, it has been found that GERD is more frequently reported by patients at the range age of 65-79 years. 13 Nevertheless, increased risk of GERD has not been always reported to be linearly correlated with increasing age. For e ample, in a study conducted by Minatsuki et al, they found that GERD is more frequently correlated by patient at the range age of 45-59 years compared to younger or older age group.…”
Section: Inducing and Aggravating Factors Of Gastroesophageal Reflux mentioning
confidence: 99%